Factors Related to The Long-Term Contraception Method Use in The Work Area of Noebeba Public Health Center, South Central Timor District - Selan, Yosina; Purnawan, Sigit; Ndoen, Enjelita M. (Universitas Nusa Cendana, 2023)
Contraceptive use is the best effort for birth control in a family regulation program. Long-Acting Contraceptive Methods (LACMs) is a contraceptive known to be successful because it provides guarantees from the risk of pregnancy in the long term. However, there is a stagnation in the birth rate because couples of childbearing age (PUS) using non-LACM often experience drops out; therefore, they need to be informed to use LACM. This research aimed to identify factors related to LACM use in the work area of the Noebeba Health Center. This research was quantitative with a cross-sectional design. This research was conducted in the work area of the Noebeba Health Center with a sample of 74 PUS using contraception. Based on the Chi-square test results, variables related to LACM use at the Noebeba Health Center were maternal age (p=0.005), mother's knowledge and husband's support (p=0.000). The variables that had no relationship were parity (p=0,336) and distance to family planning services (p=0.147). Primary health care (puskesmas) should increase promotive efforts by using informational media in language that PUS easily understands at each health integrated post (posyandu) to increase PUS' knowledge about LACM.